Swelling Equilibria and Procion Blue HERD Dye Adsorption Studies of 3,4-Epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate-Based Polymeric Gels Prepared by Photoinitiated Cationic Polymerization - Sahin, E.; Degirmeci, M.; Semdinoglu, F.; Genli, N. (Asian Journal of Chemistry, 2013)
In this study, superswelling behaviour of two different cross-linked polymer of 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane-carboxylate (EEC) monomer was investigated. The cross-linked polymer of EEC i.e., (PEEC) and EEC with cyclohexene end-functional polystyrene macromonomer (PEEC-co-PSt) were prepared by photoinitiated cationic polymerization using diphenyliodonium salt (PhI2+). The per cent swelling, equilibrium swelling, initial rate of swelling, swelling rate of constant and diffusion constant values were evaluated for PEEC and PEEC-co-PSt gel systems in dimethyl sulfoxide. PEEC and PEEC-co-PSt gels were swollen in the range 878-999 % in DMSO. The adsorption of procion blue HERD dye onto PEEC and PEEC-co-PSt in DMSO solution was investigated. The equilibrium adsorption data on reactive dye on PEEC and PEEC-co-PSt were analyzed by Langmuir and Freundlich models. The maximum adsorption capacity (qm) has been found to be 556 mg/g for PEEC and 714 mg/g for PEEC-co-PSt gels.